TVET Student’s Perception on Digital Mind Map to Stimulate Learning of Technical Skills in Malaysia - Abd Karim, Rafidah; Mustapha, Ramlee (Journal of Technical Education and Training, 2022)
Digital mind map is a digital tool that is becoming increasingly popular in today’s pedagogical visual aids. However, few empirical studies have been conducted regarding Technical and Vocational Education and Training (TVET) student’s competencies on using digital mind map in learning of their technical subjects. Hence, this survey research was designed to investigate TVET student’s perceptions on the digital mind map to stimulate their learning of technical skills in Malaysian higher learning institutions. Specifically, the objectives of the study were to identify the TVET student’s perception regarding their digital mind map competencies and to examine the relationship between the usage of digital mind and their learning achievement of technical skills. A sample of 372 TVET students were randomly selected from several public TVET higher institutions in Malaysia. The online questionnaires were designed to measure the practice of digital mind map among TVET students. The data were analysed using descriptive and inferential statistics such as frequency, percentage, mean, standard deviation and Pearson correlation. The questionnaire also included three open-ended items and the qualitative data were analysed using thematic analysis. The key finding showed that the majority of TVET students have a positive perception towards the digital mind map. In addition, the main open-ended result illustrated that the digital mind map has a potential to stimulate creativity and design thinking among TVET students in Malaysia.